Implementation of the concept of “lean production” in the sphere of state and municipal services - I. M. Savitskaya; S. V. Gorbanev; I. V. Andreyeva (Новые технологии, 2018)
The purpose of the research is to identify main directions for improving the process of providing public and municipal government services and adapting the known principles of “lean production” to MFC functioning. Theories of management and theories of quality management have made the methodological basis of the research. The conducted research has justified that the concept of “lean production” in MFC activities can have a significant impact on the quality of its functioning. The practical significance of the research results lies in the possibility of using them to improve the work of the Multifunctional Center.